PHYSICAL ACTIVITY LEVELS IN PATIENTS WITH ANOREXIA NERVOSA AND CARDIOVASCULAR COMPLICATIONS. INFORMATION OVERVIEW - Magdalena Mendak; Anna Hanslik; Agata Białek; Magdalena Domisiewicz; Monika Klimczak; Aleksandra Woskowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and aim of the study: The main purpose of this article is to show the impact of eating disorders on the level of physical activity and the occurrence of cardiovascular complications. The development of anorexia- or bulimia-type disorders leads to prospective negative outcomes in physical performance and long-term cardiological issues and leads to decrease of quality of life.. Therefore, it is crucial to identify the causes and intervene quickly to prevent severe side effects. This article reviews issues about: physical and mental health risks in individuals with eating disorders, cardiovascular complications and quality of life among the patients with eating disorders. Materials and methods: This article was based on literature gathered from various databases, including Google Scholar, ResearchGate, PubMed, ClinicalTrails, Cochrane database. The keywords anorexia nervosa, eating disorders, risk factors and cardiological complications were the basis of the review. Results: Eating disorders represent a significant public health issue and require an interdisciplinary approach. These disorders develop insidiously, pose a therapeutic challenge, and leave long-lasting side effects including cardiovascular complications. Anorexia nervosa is associated with numerous cardiovascular complications, some of which can be life-threatening. Most of these abnormalities tend to resolve once a healthy body weight is restored. Therefore, treatment should primarily focus on addressing the underlying eating disorder, with symptomatic management provided as needed.